The ROV manual : a user guide to observation-class remotely operated vehicles - Christ, Robert D. (Butterworth-Heinemann, 2007)
Many underwater operations that were once carried out by divers can now be carried out more efficiently and with less risk with Remotely Operated Vehicles (ROVs). This is the first ROV how-to manual for those involved with smaller observation class ROVs used for surveying, inspection, observation and research purposes. As ROV technology becomes increasingly efficient and affordable, their use is rapidly spreading throughout a myriad of industries, everything from aquaculture to port and harbour security to underwater crime scene investigation, marine salvage, deep sea archaeology and commercial diving even deep sea rescue missions are handled by ROVs. Any industry involved with underwater investigation and surveying will inevitably rely on these machines. The ROV Manual is the first user guide to provide complete training and knowledge on ROV operations for engineers, technicians or underwater recreational enthusiasts, whether working inland or offshore. *The first book to focus on observation class ROV underwater deployment and usage in real conditions for industrial, commercial, scientific and recreational tasks *A complete user guide to ROV operation with basic information on the usage of underwater robotics and navigation equipment to obtain mission results quickly and efficiently *Ideal for anyone involved with ROVs whether in research, business or leisure underwater activities, or for heavier offshore projects, complete with self-learning questions and answers.